LEGAL REFORMS IN INDONESIA RELATED TO "PRESIDENTIAL THRESHOLD" OF PRESIDENTIAL CANDIDATE IN LAW NO. 7/2017 CONCERNING GENERAL ELECTIONS - Wiraguna, Sidi Ahyar; Fakrulloh, Zudan Arief (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The election is the manifestation of freedom in choosing the president, vice-president and legislature parliament in a country because the elections has a role as a mechanism for political change regarding the funds patterns for the direction of public policy/or regarding the circulation of the elite periodically and in an orderly manner. Indonesia itself holds the presidential and vice-presidential elections every five years that requires its citizens to vote the potential candidates for becoming the president and vice president for the next 5 years. This research aims to find out the legal reforms related to presidential nomination of presidential threshold based on Law No. 7/2017 concerning the General Elections. This research examines the law concerning presidential elections and presidential threshold based on 1945 Constitution in Indonesia to find out the president election and the obstacles in its implementation. This research indicated that it is possible that public expect more candidate than just two candidates. Then, the public will only vote for presidential candidates from the dominant political party, not the party that suits the community's needs. The result of this research can be concluded that the unnecessary presidential appointments are incompatible with the dignity of Indonesia constitution.